A Study to Analyze the Change in Consumer Behavior towards Luxury Goods among students when exposed to Social Media Marketing with specific reference to Wrist Watches - Loya, A; Ubeja, S; Jain, P; Acharya, S; Bhosle, Pooja (International Journal of Computer Sciences and Engineering, 2025)
Social media as a platform has to a large extent been an influencing force in the current economic turnaround. The studies undertaken earlier have shown how young adults give high priority to brand consumption and the current study examines the influence of social media marketing on students towards luxury brands when exposed to advertisements released on the social network sites. The examination was conducted on a sample size of 201 respondents with a pre-exposure and proexposure to advertisement activity and paired sample T-test being applied on the responses. It was observed from the test that the respondents were influenced in taking a decision after being exposed to a message but at the same time were not influenced by the buzz created by fellow social media users.